Global challenges and manager’s competences - Marčinskas, Albinas; Diskienė, Danuta; Barčkutė, Ona (Publishing House of the Wrocław University of Economics, 2009)
We can unmistakably state that nowadays the world is facing uneasy historically unique times, when the sustainability of economic, political and social systems is challenged. This economic crisis has stepped out of the boundaries of “ordinary” crises based on previously used valuation criteria. This crisis is systematic, with hardly predictable outcomes and challenges. New words expressing ecological, food and energy problems have made their presence in the vocabulary. These global challenges are remarkably vast and dynamic. According to crisis management and system theories, these global challenges will stipulate not only the formation of new organisational structures (for instance, the creation of global economic regulation centre, as an alternative to United Nations), also the formation of new competences. This is equally important on the world, national and organisational levels. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 305-314